No, because -15 have 2 corresponding elements .
Answer:
![\dfrac{z-y}{a+b}](https://tex.z-dn.net/?f=%5Cdfrac%7Bz-y%7D%7Ba%2Bb%7D)
Step-by-step explanation:
Given expression:
![\dfrac{z^2-y^2}{a^2-b^2}\div \dfrac{z+y}{a-b}](https://tex.z-dn.net/?f=%5Cdfrac%7Bz%5E2-y%5E2%7D%7Ba%5E2-b%5E2%7D%5Cdiv%20%5Cdfrac%7Bz%2By%7D%7Ba-b%7D)
Substitute
![a^2-b^2=(a-b)(a+b)\\ \\z^2-y^2=(z-y)(z+y)](https://tex.z-dn.net/?f=a%5E2-b%5E2%3D%28a-b%29%28a%2Bb%29%5C%5C%20%5C%5Cz%5E2-y%5E2%3D%28z-y%29%28z%2By%29)
into the expression:
![\dfrac{(z-y)(z+y)}{(a-b)(a+b)}\div \dfrac{z+y}{a-b}\\ \\ \\=\dfrac{(z-y)(z+y)}{(a-b)(a+b)}\times \dfrac{a-b}{z+y}\\ \\ \\=\dfrac{z-y}{a+b}](https://tex.z-dn.net/?f=%5Cdfrac%7B%28z-y%29%28z%2By%29%7D%7B%28a-b%29%28a%2Bb%29%7D%5Cdiv%20%5Cdfrac%7Bz%2By%7D%7Ba-b%7D%5C%5C%20%5C%5C%20%5C%5C%3D%5Cdfrac%7B%28z-y%29%28z%2By%29%7D%7B%28a-b%29%28a%2Bb%29%7D%5Ctimes%20%5Cdfrac%7Ba-b%7D%7Bz%2By%7D%5C%5C%20%5C%5C%20%5C%5C%3D%5Cdfrac%7Bz-y%7D%7Ba%2Bb%7D)
If the line is perpendicular, then its slope is the reciprocal of the given line's slope. This new line's slope is 1/2. We plug it into slope-intercept form
y = 1/2x + b
Now plug in the given point of (2, 10) and solve for b.
10 = 1/2(2) + b
10 = 1 + b
9 = b
So your equation is y = 1/2x + 9
Answer:
36
Step-by-step explanation:
multiply the width & the height